Preferensi Masyarakat Desa Marikoi Terhadap Proses Layanan Melahirkan dengan Dukun Bayi Perspektif Maqasid Syariah - Astyawan, Adelia Zahratunnisa; Trihartiningsih, Evie; Ningsih, Fitriani; Anugraheni, Muchlisa; Rokhmi, Siti Nafizah (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2025)
This study discusses the preferences of Marikoi villagers in choosing TBA delivery services over medical professionals. The main factors influencing this decision are hereditary trust, affordability, and ease of access to TBAs who are closer to the community. From an obstetric perspective, this practice poses a high health risk as TBAs do not have adequate medical skills to handle labor complications. However, from a maqashid sharia perspective, the principle of protection of life (hifz an-nafs) emphasizes that the safety of mothers and babies should be the top priority. Therefore, an integration strategy between TBAs and health workers is needed so that traditional practices can still be carried out within safe limits. The government also needs to improve access to health services and educate the public on the importance of safe delivery in medical facilities. With this approach, it is hoped that maternal and infant mortality rates can be reduced without eliminating the cultural values that are still upheld by the community.